2014
DOI: 10.1136/bmjopen-2014-005554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management issues vary by specialty in the Victorian Audit of Surgical Mortality: a retrospective observational study

Abstract: ObjectiveClinical management issues are contributory factors to mortality. The aim of this study was to use data from the Victorian Audit of Surgical Mortality (VASM), an educational peer-review process for surgeons, to discover differences in the incidence of these issues between surgical specialties in order to focus attention to areas of care that might be improved.DesignThis study used retrospectively analysed observational data from VASM. Clinical management issues between eight specialties were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Admission status, delays in patient care, requirement for critical care, the number of operations performed during the admission and presence of clinical management issues have all been identified as preventable issues associated with surgical care in previous reports. [2][3][4][8][9][10][11][12][13][14] These studies have focussed upon the preventability of the individual clinical management issues instead of our methodology, which provides a more holistic approach to the audit of the mortality. The VASM has previously shown that assessors found that inappropriate absence of either venous thromboprophylaxis or critical care unit use were not significant issues (only 6 and 8%, respectively, would have benefited), which emphasizes the importance of clinical management issues rather than risk management issues when examining surgical mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Admission status, delays in patient care, requirement for critical care, the number of operations performed during the admission and presence of clinical management issues have all been identified as preventable issues associated with surgical care in previous reports. [2][3][4][8][9][10][11][12][13][14] These studies have focussed upon the preventability of the individual clinical management issues instead of our methodology, which provides a more holistic approach to the audit of the mortality. The VASM has previously shown that assessors found that inappropriate absence of either venous thromboprophylaxis or critical care unit use were not significant issues (only 6 and 8%, respectively, would have benefited), which emphasizes the importance of clinical management issues rather than risk management issues when examining surgical mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There is a subtle but important difference in preventability of individual management issues that might be responsible for the death of a patient, which is the usual approach in the ANZASM audits, as opposed to issues identified in a mortality identified as potentially preventable. Admission status, delays in patient care, requirement for critical care, the number of operations performed during the admission and presence of clinical management issues have all been identified as preventable issues associated with surgical care in previous reports . These studies have focussed upon the preventability of the individual clinical management issues instead of our methodology, which provides a more holistic approach to the audit of the mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VASM and the Victorian Coroner both aim to improve public health and safety by way of investigation of mortality . However, it is important to note that their different approaches result in different patient populations, as evident by the relatively small crossover population available for this study.…”
Section: Discussionmentioning
confidence: 99%